Effect of Friction Pressure on the Mechanical Properties of CDFW Dissimilar Aluminium 6061-T6 and Stainless steel 304 Welding Joints - Suwanda, Totok; Yulianto, Tri; Nugroho, Aris Widyo; Ardiyansyah, Nur (Semesta Teknika, 2024)
Welding technology has significantly developed in the industrial sector along with advances in manufacturing technology. The demand for joining methods combining dissimilar metals is increasing in the industrial sector. However, joining dissimilar metals is challenging because of differences in physical and mechanical properties. Continuous drive friction welding is a solid-state joining method widely used to join dissimilar metals. The research aimed to determine the effect of variations in friction pressure on the mechanical properties of continuous drive friction welding joints with dissimilar materials, Aluminum 6061 T6 and Stainless Steel 304. The process parameters used in this welding were the friction pressures used were 30 MPa, 35 MPa, and 45 MPa. The friction time is 2 seconds, the rotation speed is 1000 rpm, and the upset pressure is 50 MPa. Then, welded joints were evaluated for Vickers microhardness and microstructure observations. Based on the research results, it shows that the temperature distribution and microstructure results show that there is a change in the hardness value of the aluminum material. In contrast, the 304 stainless steel material experiences an insignificant change in the hardness value.